The Impact of the 2022 Electoral Reform on the Credibility of the 2023 General Elections in Nigeria - Tsokwa, Solomon; Nwanegbo, C. Jaja (International Journal of Education, Culture, and Society, 2024)
Over the years, Nigeria has faced serious election fraud, leading many Nigerians to lose confidence in the electoral process. In 2022, the new Electoral Act was introduced, creating more opportunities for the integration of technologies like BVAS and IREV to improve voter accreditation, result transmission, and real-time election viewership for all stakeholders. This development was welcomed by many Nigerians who hoped the Act would restore voter confidence in the country. However, the outcome of the elections, particularly the presidential elections, indicated that the Act failed to meet the expectations of Nigerians. This study therefore examined the Electoral Act 2022 and the election credibility of the 2023 elections. It explored why the Act failed to mitigate insecurity and ensure effective transmission and viewing of election results, which are key to free and fair elections. Using a mixed research approach to data collection and analysis, the study drew on direct responses from voters and stakeholders, scholarly literature, media reports, and findings from election observer groups. The results indicate that while the Act provides a legal framework for stronger elections in Nigeria, it has not sufficiently ensured a free and fair election in the presidential polls. The study concludes that the Act alone cannot guarantee transparent elections due to poor implementation by stakeholders and certain grey areas in the Act that were exploited for election manipulation. The researcher recommends revisiting or strengthening these grey areas to prevent manipulation by elites and ensuring effective implementation by all stakeholders. Specifically, the study suggests the integration of technological advancements, such as blockchain for secure voting, electronic voting systems to enhance accessibility, geospatial technology for better logistics management, and secure mobile applications for real-time results transmission, to further bolster election credibility and transparency in Nigeria.